Functional capacity evaluations as a post-offer employment: a case study. - Ratzon NZ (Work, 2004)
Functional capacity evaluations in the post-offer phase of employment has the capacity to minimize work related injuries and promote wellness on the worksite. This paper includes a discussion of the value of post-offer evaluations and possible assessment options. To investigate the feasibility of administering post-offer evaluations, a case study was initiated. The Physical Work Performance Evaluation (PWPE) was administered to a new employee, VA, who was employed for the task of kneading dough, at a major food company. When compared to detailed work demands, there was no match between the job demands, and the client's capability in two sub-tests: lift from waist to eye level and trunk rotation. Based upon findings, recommendations for an initial graded work schedule, basic strengthening exercises, and modifications of the job site and task were made to the employer. The project was initiated with the hope of raising employee's and employer's awareness of workers health issues in the post-offer phase as it express itself in post-offer evaluation that aims to prevent musculoskeletal problems. This article aims to expand occupational therapists' awareness to the potential benefits of such a process.